Alprostadil for the treatment of impotence. (February 2014) - Hanchanale, Vishwanath; Eardley, Ian
<x xml:space="preserve">Abstract</x> Introduction: Erectile dysfunction (ED) affects over 150 million men worldwide. Oral phosphodiesterase-5 (PDE5) inhibitors are currently used as a first-line therapy and a second-line therapy with either intracavernosal (Caverject) or intraurethral (MUSE) <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=Alprostadil&logicalOpe1=OR&field2=articletitle&text2=Alprostadil&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">alprostadil is required for a few men who show poor response or intolerance to PDE5 inhibitors. Areas covered: This article reviews the pharmacology, pharmacokinetics, medical applications, efficacy and safety of alprostadil in the treatment of men with ED. The goal of this article is to review the currently published clinical data of alprostadil to establish its potential role in managing men, in particular, those who fail to respond to traditional PDE5 inhibitors. Relevant articles and abstracts were reviewed from PUBMED and conference proceedings. Expert opinion: Alprostadil, a synthetic form of prostaglandin E1, is used as second-line therapy in managing men with ED. It has a unique role in men with ED secondary to diabetes and ED secondary to radical pelvic surgery (e.g., radical prostatectomy). In view of these new indications, the role of alprostadil is being redefined. Both intracavernosal and intraurethral alprostadil are approved for use in all countries, and following positive results from recent Phase III trials, topical alprostadil has gained approval in Canada.